Genome-wide association study (GWAS) reveals the genetic architecture of four husk traits in maize. (December 2016) - Cui, Zhenhai; Luo, Jinhong; Qi, Chuangye; Ruan, Yanye; Li, Jing; Zhang, Ao; Yang, Xiaohong; He, Yan
Abstract Background Maize (Zea mays) husk referring to the leafy outer enclosing the ear, plays an important role in grain production by directly contributing photosynthate and protecting ear from pathogen infection. Although the physiological functions related to husk have been extensively studied, little is known about its morphological variation and genetic basis in natural population. Results Here we utilized a maize association panel including 508 inbred lines with tropical, subtropical and temperate backgrounds to decipher the genetic architecture attributed to four husk traits, i.e. number of layers, length, width and thickness. Evaluating the phenotypic diversity at two different environments showed that four traits exhibit broadly natural variations and moderate levels of heritability with 0.64, 0.74, 0.49 and 0.75 for number, length, width and thickness, respectively. Diversity analysis indicated that different traits have dissimilar responses to subpopulation effects. A series of significantly positive or negative correlations between husk phenotypes and other agronomic traits were identified, indicating that husk growth is coordinated with other developmental processes. Combining husk traits with about half of a million of single nucleotide polymorphisms (SNPs) via genome-wide association study revealed a total of 9 variants significantly associated with traits atP < 1.04 × 10-5, which are implicated in multiple functional categories, such as cellular trafficking, transcriptional regulation and metabolism. Conclusions These results provide instrumental information for understanding the genetic basis of husk development, and further studies on identified candidate genes facilitate to illuminate molecular pathways regulating maize husk growth.